A review on qualitative assessment of natural gas utilisation options for eliminating routine Nigerian gas flaring - Abu, Robin; Patchigolla, Kumar; Simms, Nigel J. (MDPI, 2023)
Natural gas flaring, with its harmful environmental, health, and economic effects, is common in the Nigerian oil and gas industry because of a lower tax regime for flared gases. Based on the adverse effects of flared gas, the Nigerian government has renewed and improved its efforts to reduce or eliminate gas flaring through the application of natural gas utilisation techniques. However, because the conventional approach to flare gas utilisation is heavily reliant on achieving scale, fuel, and end-product prices, not all technologies are technically and economically viable for typically capturing large and small quantities of associated gas from various flare sites or gas fields (located offshore or onshore). For these reasons, this paper reviews and compares various flare gas utilisation options to guide their proper selection for appropriate implementation in the eradication of routine gas flaring in Nigeria and to promote the Zero Routine Flaring initiative, which aims to reduce flaring levels dramatically by 2030. A qualitative assessment is used in this study to contrast the various flare gas utilisation options against key decision drivers. In this analysis, three natural gas utilisation processes—liquefied natural gas (LNG), gas to wire (GTW), and gas to methanol (GTM)—are recommended as options for Nigeria because of their economic significance, technological viability (both onshore and offshore), and environmental benefits. All these gas utilisation options have the potential to significantly reduce and prevent routine gas flaring in Nigeria and can be used separately or in combination to create synergies that could lower project costs and product market risk. This article clearly identifies the environmental benefits and the technical and economic viability of infrastructure investments to recover and repurpose flare gasses along with recommendation steps to select and optimise economies of scale for an associated natural gas utilisation option.
Keywords: utilisation; gas flaring; Nigeria; routine; options; sustainable development